Impact Of Perceived Work-Life Benefit Usefulness On Organizational Citizenship Behavior (OCB): The Mediating Role Of Perceived Organizational Support (POS) - Wijewantha, P. (11th International Conference on Business Management - 2014, University of Kelaniya, Sri Lanka. p.361., 2014)
This study proposed and tested a model that links perceived work-life benefit usefulness with OCB based on the Social Exchange Theory (SET), and it also proposes that the direct relationship is mediated by Perceived Organizational Support (POS). SET supports the possibility that perceived usefulness of work-life benefits would promote employee OCBs as workers may feel obligated to exert „extra‟ effort in return for „extra‟ useful benefits. The study was designed to investigate why the female school teachers of international schools do not demonstrate desired OCBs. A significant positive relationship was found between perceived work-life benefit usefulness and OCB and that relationship was partially mediated by POS. The study is done among 212 female teachers of international schools located in the Western province of the country. Data were collected using an anonymous selfadministered questionnaire filled by the teachers and their respective officers-in-charge. Data were analyzed using SPSS version 17.0 where simple regression analysis was used to test the direct relationship and four step three regressions approach was used for the mediator test. This study is of immense significance for the managements of non-governmental schools as they require high levels of employee commitment to ensure quality of service to the satisfaction of students and their parents to face the competition amidst the large number of such schools in the country at present. Though the potential to produce the desired effects is obvious, research is yet to address the issue in the present context, and this study fills that void in research.
Keywords: Organizational Citizenship Behavior (OCB); Perceived Organizational Support (POS); Perceived Work-Life Benefit Usefulness